The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ajpa.22454
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic reconstructions of adult diets and infant feeding practices during urbanization of the city of Edo in 17th century Japan

Abstract: The urbanization of the city of Edo, the capital of premodern Japan, has been assumed to be not as a result of natural increase but that of in-migration although this assumption has never been verified. To obtain information on natural fertility in Edo, we analyzed stable carbon and nitrogen isotopes in 46 adult and 84 subadult human skeletons excavated from the Hitotsubashi site (1657-1683 AD: the early Edo period), Tokyo, Japan and reconstructed their breastfeeding period, one of the most important determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…Previous studies indicated that there is no significant isotopic difference among adult skeletons in different ages for an Edo period population Tsutaya et al, 2014bTsutaya et al, , 2016, which suggests that δ 13 C and δ 15 N values do not apparently differ as a result exclusively of the different stages of life history after adulthood. Because ST61 moved from Echizen to Akashi at 27 years of age (Saito, 1954;Shigematsu, 1981;Tsuda, 1994), the differences in ecological isotopic baselines and/or dietary practices could account for this difference.…”
Section: Dietary Changementioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies indicated that there is no significant isotopic difference among adult skeletons in different ages for an Edo period population Tsutaya et al, 2014bTsutaya et al, , 2016, which suggests that δ 13 C and δ 15 N values do not apparently differ as a result exclusively of the different stages of life history after adulthood. Because ST61 moved from Echizen to Akashi at 27 years of age (Saito, 1954;Shigematsu, 1981;Tsuda, 1994), the differences in ecological isotopic baselines and/or dietary practices could account for this difference.…”
Section: Dietary Changementioning
confidence: 91%
“…Several historical documents of this period, such as Shoni hitsuyo sodate-gusa published in 1703, recommended that infants should be gradually weaned and breastfed until approximately 3 years of age (Yamazumi and Nakae, 1976;Sone, 2011; see also Tsutaya et al, 2014b). A previous isotopic study of subadult bone collagen indicated a gradual weaning process, with 2.1-4.1 years being the weaning end age in the Hitotsubashi population of Tokyo in the earlier Edo period (Tsutaya et al, 2014b). A gradual weaning process was also reported in another isotopic study for the Fushimi population in Kyoto during the entire Edo period .…”
Section: Breastfeeding Weaning and Diet In Subadulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…investigated BWPs in a hunter-gatherer population in Epi-Jomon Japan (2300-1700 years BP), and revealed different infant feeding practices in the population. Tsutaya et al (2014) showed relatively longer breastfeeding periods in the city of Edo in 17th century Japan, and inferred that the urbanization of Edo was achieved by immigration and not by natural population increase.…”
Section: Applications Studied Tissuesmentioning
confidence: 97%
“…Shorter breastfeeding periods tend to result in shorter birth intervals and higher fertility because suckling stimuli and the energetic burden of lactogenesis can delay the resumption of a mother's ovulation (Vitzhum, 1994;Wood, 1994;Valeggia and Ellison, 2009;WHO, 2009). Breastfeeding periods in ancient human populations have been reconstructed as a proxy of fertility in ancient demographic events (e.g., Schurr and Powell, 2005;WatersRist et al, 2011;Tsutaya et al, 2014).…”
mentioning
confidence: 99%